2005
DOI: 10.1007/s11864-005-0035-9
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid cancer: Surgical management of lymph node metastases

Abstract: Papillary thyroid cancer (PTC), the most common thyroid malignancy, is associated with cervical lymph node metastases in 30% to 90% of patients. While surgery is the primary treatment modality for PTC, radioactive iodine and thyroid hormone suppression often complement the treatment plan. Although thyroid hormone suppression may decrease the incidence of recurrent disease and radioactive iodine may diagnose and treat metastases, lymph node dissection (LND) is the mainstay treatment for clinically evident cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 33 publications
2
92
1
4
Order By: Relevance
“…Most of node metastasis at level V belong to pN1b, so prophylactic dissection of level V also has only limited clinical importance. levels II, III, and IV were the most frequent with clinically positive lymph node (Caron et al, 2006), our study also have the similar results, Seventeen (36.12%), 36 (76.6%), and 34 (72.34%) patients had positive lymph nodes in levels II, III, and IV, respectively.some studies evaluated the potential predictor factors (Caron et al, 2006), revealed that patients with simultaneous metastases to levels II, III, and IV had greater node metastasis at level V (Caron et al, 2005;Roh et al, 2008), these node metastasis at level V all belong to pN1b, the clinical benefits from level V dessection guided by simultaneous metastases is still controversial. And more patients would not benefit from this dissection while would face postoperative morbidity.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Most of node metastasis at level V belong to pN1b, so prophylactic dissection of level V also has only limited clinical importance. levels II, III, and IV were the most frequent with clinically positive lymph node (Caron et al, 2006), our study also have the similar results, Seventeen (36.12%), 36 (76.6%), and 34 (72.34%) patients had positive lymph nodes in levels II, III, and IV, respectively.some studies evaluated the potential predictor factors (Caron et al, 2006), revealed that patients with simultaneous metastases to levels II, III, and IV had greater node metastasis at level V (Caron et al, 2005;Roh et al, 2008), these node metastasis at level V all belong to pN1b, the clinical benefits from level V dessection guided by simultaneous metastases is still controversial. And more patients would not benefit from this dissection while would face postoperative morbidity.…”
Section: Discussionsupporting
confidence: 84%
“…As the wide use and satisfactory diagnostic efficacy, high resolution ultrasonograpy has been used to detect lateral positive lymph node (Robbins et al, 2002;Caron et al, 2005;Ito et al, 2005;Cooper et al, 2006;Doherty et al, 2009). Nowadays, clinically positive lymph node metastasis includes the nodes detected both by palpation and ultrasonograpy (Caron et al, 2006), and ultrasonograpy is more sensitive than palpation, the proportion of clinically positive lymph node detected by ultrasonograpy becomes greater, we would think that the severity of cN1b detected by ultrasonograpy is less than that by palpation, and would be expected to have lower recurrrence and better survival.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies report that the initial lymph node is involved in 30-90% of patients, and it is revealed by pathologic examination that there were high rates of central CLNM (57.9%) and lateral CLNM (25.6%) in patients with PTC (Kupferman et al, 2004;Caron et al, 2005;Roh et al, 2009). Patients with CLNM have an increased chance of recurrence and a low survival rate (Beasley et al, 2002;Mazzaferri et al, 2003;Machens et al, 2003;Lundgren et al, 2006;Ito et al, 2009;Rotstein, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…3 Selective berry picking of nodes is not recommended as that leads to higher recurrences. 4 By learning fine details of techniques of doing meticulous neck dissections, we can minimize morbidity as well as ensure best cure rates by doing R0 resections 5,6 In patients with thyroid cancer, recurrences happen in 20 to 30% of the patients and most recurrences are due to insufficient initial surgery. 7 Hence, it is very important to understand finer details of doing neck dissections in thyroid cancer to achieve best possible cure rates.…”
Section: Discussionmentioning
confidence: 99%